2021
DOI: 10.3390/microorganisms9030638
|View full text |Cite
|
Sign up to set email alerts
|

The Ubiquitination System within Bacterial Host–Pathogen Interactions

Abstract: Ubiquitination of proteins, like phosphorylation and acetylation, is an important regulatory aspect influencing numerous and various cell processes, such as immune response signaling and autophagy. The study of ubiquitination has become essential to learning about host–pathogen interactions, and a better understanding of the detailed mechanisms through which pathogens affect ubiquitination processes in host cell will contribute to vaccine development and effective treatment of diseases. Pathogenic bacteria (e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 167 publications
0
16
0
Order By: Relevance
“…The RING E3 ligases promote the transfer of ubiquitin directly from E2 to the substrate, while the HECT and RBR ligases have a conserved cysteine residue where the ubiquitin binds before being transferred to the substrate, thus forming an intermediate E3-Ub. However, RBR ligases have interaction domains similar to those present in RING ligases [ 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…The RING E3 ligases promote the transfer of ubiquitin directly from E2 to the substrate, while the HECT and RBR ligases have a conserved cysteine residue where the ubiquitin binds before being transferred to the substrate, thus forming an intermediate E3-Ub. However, RBR ligases have interaction domains similar to those present in RING ligases [ 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…While ubiquitylation has been studied for many years in the endosomal system for its role in receptor sorting and multi-vesicular body (MVB) formation (Frankel & Audhya, 2018, Haglund & Dikic, 2012), and significant work has gone into characterising bacterial ubiquitin enzymes of intracellular pathogens such as Legionella (Vozandychova et al, 2021), little is known about the role of endogenous ubiquitylation on the phagosome. In 2005, it was shown that ubiquitin accumulates around the phagosome and that loss of E1 activity resulted in accumulation of Fc-receptors, suggesting a defect in the sorting of these receptors (Lee et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, few pathogens are known to actively modify surface proteins, protecting them from ubiquitination and subsequent killing, thus emphasizing the significance of surface localization of the ubiquitin substrate (4). Additionally, multiple obligate intracellular pathogens have evolved strategies to de-ubiquitinate themselves or host regulatory components to evade ubiquitin mediated clearance (24). Taken together, these underscore ubiquitin-mediated alarm arousal as a fundamental intracellular pathogen sensing mechanism central to host defenses.…”
Section: Main Textmentioning
confidence: 99%